Advanced ship design for pollution prevention : International Workshop Advanced Ship Design for Pollution Prevention 23 and 24 November 2009 Split, Croatia - Proceeding of the International Workshop "Advanced ship design for pollution prevention" (23-24 November 2009 : Split, Croatia) 526395; Soares, Carlos Guedes 401268; Parunov, Josko 524450 (Leiden, Netherlands : CRC Press, 2010)
Includes bibliographical references and index